Agendas, institutions and strategies in the FODESAF creation, notes for the study of the "exceptionality" of Costa Rican social policy - Solano-Chavarría, Héctor (2012)
Part of the reasons for the Costa Rican “exceptionality” in the social sphere are linked to the 1970’s context, the “golden age” of Costa Rica’s regime of social policy. This study explores the origins and factors of the “golden age” through analyzing the development of one of the emblematic policies of the time (FODESAF, 1974.) This will demonstrate that the configuration of a policy community that was closed to the participation of formal actors on institutional grounds –within an exclusion of trade union and business actors from such policy– explained the policy’s feasibility. Considering how literature emphasizes tripartite designs in the creation of social policies, this study helps questioning –from the Costa Rican experience– the common senses tied to the type of political arrays necessary to formulate regimes that are successful and capable of enduring structural changes introduced by the neoliberal model.